KEHIDUPAN PEDESAAN DAN PERKOTAAN DAYAK SARAWAK - Albertus; Sophia Lubis, Mira (JURNAL BORNEO AKCAYA, 2016)
The paper envisages rural and urban life of Sarawak Dayak by describing the ways in which the living spaces, job specialization and social interaction shaped them. The urban life promised attraction of good amenities such as university, economic development, transportation networking, health service, prosperity and livelihood improvement. Those trigger the flows of people and goods. Then, city faced serious problems such as traffic congestion, garbage, jobless, slum dwellers, squatter settlements, and social tension. To minimize the city’s problems, it must be seen as organic order, when the correlative and expressive faculties are potent enough to maintain organic order, the problems can be handled. In this binary, a rural life is portrayed as mountainous area in which the villagers live in the longhouse and practice customary law. In this situation, the mechanism of life will be able to run independently because the village life is like mechanic which can be separated each other. The study refers to the description living spaces named rural and urban spaces, in which these two living spaces need one another. Longhouse and village became city for the inhabitants in the past, and nowadays, modern city become a place for livelihood to replace farming ground. Furthermore, the description of living spaces and the peoples, the factors which have the contribution to fade rural and urban distinction identified.